2017
DOI: 10.1080/17461391.2017.1405077
|View full text |Cite
|
Sign up to set email alerts
|

Ergogenic effects of precooling with cold water immersion and ice ingestion: A meta‐analysis

Abstract: This review evaluated the effects of precooling via cold water immersion (CWI) and ingestion of ice slurry/slushy or crushed ice (ICE) on endurance performance measures (e.g. time-to-exhaustion and time trials) and psychophysiological parameters (core [T] and skin [T] temperatures, whole body sweat [WBS] response, heart rate [HR], thermal sensation [TS], and perceived exertion [RPE]). Twenty-two studies were included in the meta-analysis based on the following criteria: (i) cooling was performed before exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 79 publications
2
30
1
Order By: Relevance
“…In conclusion, this meta-analysis has provided several novel fi ndings. First, it does not support a recent review (Choo et al, 2018) on this topic. Ice slurry ingestion provides a signifi cant benefi t for endurance performance in the heat, and this eff ect is moderate in magnitude (g=0.54).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In conclusion, this meta-analysis has provided several novel fi ndings. First, it does not support a recent review (Choo et al, 2018) on this topic. Ice slurry ingestion provides a signifi cant benefi t for endurance performance in the heat, and this eff ect is moderate in magnitude (g=0.54).…”
Section: Discussionmentioning
confidence: 65%
“…Given that environmental heat and humidity can severely limit performance, hence medal chances, in elite competition, optimizing ice slurry ingestion is of interests to elite athletes participating in endurance events. Currently, there is no consensus regarding the dose-response relationship, timing strategy, and infl uences of diff erent environmental temperature and humidity conditions (Bongers et al, 2015;Choo, Nosaka, Peiff er, Ihsan, & Abbiss, 2018). Accordingly, this meta-analysis explored up-to-date evidence on how eff ective ice slurry ingestion could enhance endurance performance in the heat, and in particular, highlighted key intervention strategies that could infl uence its eff ect.…”
Section: Introductionmentioning
confidence: 99%
“…Many athletes commonly use pre-cooling techniques (Figure 3; Périard et al, 2017), a strategy that may seem counterproductive and potentially incompatible with warmingup. Pre-cooling refers to the lowering of pre-exercise body temperatures to lower thermal strain during the ensuing exercise task (Marino, 2002;Choo et al, 2018). A 0.5 • C decrease in pre-exercise core temperature is often the desired goal of a precooling strategy, whilst a 0.3 • C decrease is generally considered the physiological minimum to confer a thermoregulatory advantage (Marino, 2002).…”
Section: Warm-up or Pre-cooling Before Competition?mentioning
confidence: 99%
“…Th us, the test results from Zimmermann and Landers (2015) does not relate to the purpose of their meta-analysis. Notably, the aforementioned four studies all reported nonsignifi cant performance eff ects (Choo et al, 2018). Taken together, four out of eleven meta-analyzed studies were poor selection of the relevant literature, which biased the main results.…”
Section: Methodsmentioning
confidence: 96%
“…In a paper published in European Journal of Sport Science in 2018, Choo, Nosaka, Peiff er, Ihsan, and Abbiss (2018) concluded that ice slurry ingestion had no clear eff ect (Hedges' g, 0.2; 95% confi dence interval, −0.07 to 0.46) on endurance performance. I am not convinced of the validity of their literature selection and have great concern about what has been conveyed to those readers relying on science to guide their practice in the fi eld.…”
Section: Introductionmentioning
confidence: 99%